Embedded systems technology : 15th National Conference, ESTC 2017, Shenyang, China, November 17-19, 2017, Revised selected papers /: 15th National Conference, ESTC 2017, Shenyang, China, November 17-19, 2017, Revised selected papers. (2018) - Unknown
No abstract available